The Affective Core of the Self: A Neuro-Archetypical Perspective on the Foundations of Human (and Animal) Subjectivity - Alcaro, Antonio; Carta, Stefano; Panksepp, Jaak (Frontiers in Psychology, 2017)
Psychologists usually considered the “Self” as an object of experience appearing when the subject begins to perceive its existence within the conscious field. In accordance with such view, the self-representing attitude of the human mind has been usually related to individual development and to neuro-plastic acquisitions of the cortico-limbic network. On the other hand, Carl Gustav Jung considered the Self as the inborn dynamic core of our personality, in its conscious and unconscious aspects as well as in its actual and potential forms. According to Jung, the Self integrates those essential bio-psychological drives leading to instinctual behavioral actions and archetypal psychological experiences and influencing all forms of learning and memory. Interestingly, recent neuroethological studies indicate that our subjective identity rests on ancient neuro-psychic processes that humans share with other animals as part of their inborn constitutional repertoire. Indeed, the brain activity within subcortical midline structures (SCMS) is intrinsically related to the emergence of prototypical affective states, that influence our behavior in a flexible way and alter our conscious field, giving rise to specific feelings or moods, which constitute the first form of self-orientation in the world. Moreover, such affective dynamics play a central role in the organization of individual personality, informing about the meaning of our personal experience and harmonizing our instinctual vestiges within the experience-dependent learning functions of the “mind-brain”. Therefore, on the base of the convergence between contemporary cutting-edge scientific research and some psychological intuition of Jung, we intend here to explore the first neuro-evolutional layer of human mind, that we call the affective core of the Self.